Isolation of Bacteria from Psophocarpus Tetragonolobus and Biofilm Formation - J., Nur Syifa',; R., Kahsalya Devi,; A., Dhuha Saeed,; N. A., Mahyudin,; M. A. R., Nor-Khaizura, (Journal of Science and Technology, 2017)
Vegetables are easily spoiled by different microorganisms with bacterial and fungal species during processing. Usually, vegetables are serving as carrier for pathogenic bacteria, parasites and viruses and lead to food borne illness outbreaks. The winged bean (Psophocarpus tetragonolobus) species is goes to the genus Psophocarpus, a tropical legume plant commonly known as the Goa bean, Manila bean, four-angled bean or four-cornered bean and Mauritius bean. The ability of bacteria to attached on surfaces and form a distinct biofilm can lead to food spoilage. Biofilm formation relies on three main parameters including the bacterial cells, the surface attached, and the surrounded medium but the attachment of bacteria to the surface is the initial process of biofilm. This research conducted to isolate bacteria from the winged bean and to determine biofilm formation. Throughout the study, four different types of bacteria were isolated from winged bean such E. coli, Listeria, Salmonella, and Shigella. Then, all the isolated bacteria were further analyzed for biofilm formation. As the results, only E. coli bacteria show the ability to form a biofilm on winged bean at room temperature. The other bacteria such as Listeria, Salmonella, and Shigella have not shown the biofilm formation. This could be due to the environment, temperature or the sample size which not being favourable factors for the formation. However, there is an urgent need to ensure the microbiological safety in food industries, especially in processed foods, like fresh-cut vegetables, in such a way that the lack of heat treatment does not promote the growth of potentially pathogenic microorganisms.